Dinobryon faculiferum (Chrysophyta) in coastal Mediterranean seawater: Presence and grazing impact on bacteria - Unrein, Fernando (2010)
We report the presence and abundance of Dinobryon faculiferum (Chrysophyta) in NW Mediterranean coastal waters, as well as the first estimations of the grazing impact of this mixotrophic species on bacteria. In June 2006, D. faculiferum was detected at an abundance of 37 cell mL-1 (1.2 of total protistan abundance). By grazing with cell-specific rates of 7.8 bacteria cell h-1, this single species explained 4.5 of the total bacterial grazing losses.